1989
DOI: 10.1113/jphysiol.1989.sp017825
|View full text |Cite
|
Sign up to set email alerts
|

Task‐dependent changes in cutaneous reflexes recorded from various muscles controlling finger movement in man.

Abstract: 1. Cutaneous reflex responses have been recorded from muscles involved in the control of finger movement following electrical stimulation of the digital nerves of the fingers in man. 2. Recordings have been made while subjects performed various manual tasks. 3. Reflexes recorded while subjects performed a relatively isolated finger movement consisted of an initial short-latency increase in muscle electrical activity, followed by a decrease, followed by a prominent longer-latency increase. The long-latency exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 16 publications
5
54
2
Order By: Relevance
“…Previous studies have shown that CMRs are dependent upon the ongoing motor task (Evans et al 1989), exhibit habituation and can be modulated during acquisition of a new motor skill (Nadler et al 2000). In this study we report attenuation of the transcortical E2 component of the CMR during finger movement.…”
Section: Department Of Physiology University College London Cower Ssupporting
confidence: 51%
“…Previous studies have shown that CMRs are dependent upon the ongoing motor task (Evans et al 1989), exhibit habituation and can be modulated during acquisition of a new motor skill (Nadler et al 2000). In this study we report attenuation of the transcortical E2 component of the CMR during finger movement.…”
Section: Department Of Physiology University College London Cower Ssupporting
confidence: 51%
“…For example, selective simulation of digital nerves in the index finger are known to evoke cutaneomuscular reflexes in the first dorsal interosseus muscle (cf. Evans et al, 1989;Turner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several manipulations have been performed to convert the rectified averaged SEMG record for this purpose. For example, Goldberg (1971) used a planimeter to measure the area of the rectified averaged SEMG record; van der Glas and colleagues (1984) used the sum of the absolute surfaces outside the confidence interval (total normalized surface, TNS); Evans and colleagues (Evans et al ., 1989) used the percentage modulation of the mean SEMG level as the calibration bar; and Cadden and Newton (1994) calculated the area to indicate the percentage change. Quantification of the synaptic potentials from the SEMG data can be criticized for two main reasons:…”
Section: S Urface Electromyogram(semg)mentioning
confidence: 99%